The challenges of using the WebCAPE placement exam in an advanced Spanish grammar class. Issue 3 (19th May 2017) - Turner III, Robert L.
ABSTRACT: This study attempts to ascertain if the WebCAPE placement exam can be used to measure improvement in an upper division grammar course. The WebCAPE online placement exam is a widely used instrument designed to help university language programs place students into the basic language course best corresponding to their proficiency level. This is done through computerized adaptive language testing optimized for students in the first four semesters of basic language instruction. In this study the researcher employed this placement exam in the context of an advanced Spanish grammar class. The study revealed that the WebCAPE produces statistically significant results when correlated to final grade, test average, and the second administration of the placement exam at the end of the semester. However, the effect sizes for the predictive elements were small. It was further observed that for participants who initially placed above the recommended cut-off for higher than third semester Spanish, there was a moderately negative correlation between initial placement score and class performance. It is speculated that the nature of the placement exam produces a ceiling effect that reduces its placement value for classes beyond basic Spanish.